Kesalahan Berbahasa dalam Modul I Bahasa Indonesia PPG Dalam Jabatan Tahun 2020 - Rahmad Hidayat (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
This research is here to explain several forms of errors in the material module of the Pendidikan Profesi Guru Dalam Jabatan Tahun 2020. Research on the analysis of language errors in the PPG module has never been carried out. In data collection, used the Listening method with the Note Technique. The data are recorded in such a way in tabulations. In analyzing the data, the Intralingual Matching method was used with HBS and HBB techniques. HBS and HBB techniques are realized by comparing between language data and applicable rules. Furthermore, deviant linguistic data are classified based on the types of violations against linguistic rules and theories. The presentation of the results of data analysis in this study is based on the taxonomy of linguistic categories in language error analysis. The results showed that in the module I PPG Dalam Jabatan Tahun 2020 there were spelling errors in the form of punctuation errors, capital letters errors, italicization errors, and word writing errors; morphological errors in the form of word formation errors and word non-conformity; syntactic errors in the form of misuse of conjunctor and ineffective sentences.